Preservation versus non-preservation of mitral valve apparatus during mitral valve replacement: a meta-analysis of 3835 patients - Sá, Michel Pompeu Barros de Oliveira (Oxford University Press, 2012)
Resection of the chordopapillary apparatus during mitral valve replacement has been associated with a negative impact on survival. Mitral valve replacement with the preservation of the mitral valve apparatus has been associated with better outcomes, but surgeons remain refractory to its use. To determine if there is any real difference in preservation vs non-preservation of mitral valve apparatus during mitral valve replacement in terms of outcomes, we performed a systematic review and meta-analysis using MEDLINE, EMBASE, CENTRAL/CCTR, SciELO, LILACS, Google Scholar and reference lists of relevant articles to search for clinical studies that compared outcomes (30-day mortality, postoperative low cardiac output syndrome or 5-year mortality) between preservation vs non-preservation during mitral valve replacement from 1966 to 2011. The principal summary measures were odds ratios (ORs) with 95% confidence interval and P-values (that will be considered statistically significant when <0.05). The ORs were combined across studies using a weighted DerSimonian–Laird random-effects model. The meta-analysis was completed using the software Comprehensive Meta-Analysis version 2 (Biostat Inc., Englewood, NJ, USA). Twenty studies (3 randomized and 17 non-randomized) were identified and included a total of 3835 patients (1918 for mitral valve replacement preservation and 1917 for mitral valve replacement non-preservation). There was significant difference between mitral valve replacement preservation and mitral valve replacement non-preservation groups in the risk of 30-day mortality (OR 0.418, P <0.001), postoperative low cardiac output syndrome (OR 0.299, P <0.001) or 5-year mortality (OR 0.380, P <0.001). No publication bias or important heterogeneity of effects on any outcome was observed. In conclusion, we found evidence that argues in favour of the preservation of mitral valve apparatus during mitral valve replacement.